Transcriptome Response to Cadmium Exposure in Barley (Hordeum vulgare L.) - Kintlová, Martina; Vrána, Jan; Hobza, Roman; Blavet, Nicolas; Hudzieczek, Vojtěch (Frontiers in Plant Science, 2021)
Cadmium is an environmental pollutant with high toxicity that negatively affects plant growth and development. To understand the molecular mechanisms of plant response to cadmium stress, we have performed a genome-wide transcriptome analysis on barley plants treated with an increased concentration of cadmium. Differential gene expression analysis revealed 10282 deregulated transcripts present in the roots and 7104 in the shoots. Among them, we identified genes related to reactive oxygen species metabolism, cell wall formation and maintenance, ion membrane transport and stress response. One of the most upregulated genes was PLANT CADMIUM RESISTACE 2 (HvPCR2) known to be responsible for heavy metal detoxification in plants. Surprisingly, in the transcriptomic data we identified four different copies of the HvPCR2 gene with a specific pattern of upregulation in individual tissues. Heterologous expression of all five barley copies in a Cd-sensitive yeast mutant restored cadmium resistance. In addition, four HvPCR2 were located in tandem arrangement in a single genomic region of the barley 5H chromosome. To our knowledge, this is the first example showing multiplication of the PCR2 gene in plants.